High inter‐follicular spatial co‐localization of CD8+FOXP3+ with CD4+CD8+ cells predicts favorable outcome in follicular lymphoma. Issue 4 (28th April 2022) - Hagos, Yeman B.; Akarca, Ayse U.; Ramsay, Alan; Rossi, Riccardo L.; Pomplun, Sabine; Ngai, Victoria; Moioli, Alessia; Gianatti, Andrea; Mcnamara, Christopher; Rambaldi, Alessandro; Quezada, Sergio A.; Linch, David; et al.
Abstract: The spatial architecture of the lymphoid tissue in follicular lymphoma (FL) presents unique challenges to studying its immune microenvironment. We investigated the spatial interplay of T cells, macrophages, myeloid cells and natural killer T cells using multispectral immunofluorescence images of diagnostic biopsies of 32 patients. A deep learning‐based image analysis pipeline was tailored to the needs of follicular lymphoma spatial histology research, enabling the identification of different immune cells within and outside neoplastic follicles. We analyzed the density and spatial co‐localization of immune cells in the inter‐follicular and intra‐follicular regions of follicular lymphoma. Low inter‐follicular density of CD8+FOXP3+ cells and co‐localization of CD8+FOXP3+ with CD4+CD8+ cells were significantly associated with relapse ( p = 0.0057 and p = 0.0019, respectively) and shorter time to progression after first‐line treatment (Logrank p = 0.0097 and log‐rank p = 0.0093, respectively). A low inter‐follicular density of CD8+FOXP3+ cells is associated with increased risk of relapse independent of follicular lymphoma international prognostic index (FLIPI) ( p = 0.038, Hazard ratio (HR) = 0.42 [0.19, 0.95], but not independent of co‐localization of CD8+FOXP3+ with CD4+CD8+ cells ( p = 0.43). Co‐localization of CD8+FOXP3+ with CD4+CD8+ cells is predictors of time to relapse independent of the FLIPI score and density of CD8+FOXP3+ cells ( p = 0.027, HR = 0.0019 [7.19 × 10 −6, 0.49], This suggests a potential role of inter‐follicular CD8+FOXP3+ and CD4+CD8+ cells in the disease progression of FL, warranting further validation on larger patient cohorts.